2023
DOI: 10.1097/pai.0000000000001102
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen/Progesterone Receptor Loss, CTNNB1 and KRAS Mutations Are Associated With Local Recurrence or Distant Metastasis in Low-Grade Endometrial Endometrioid Carcinoma

Abstract: A subset of endometrial endometrioid carcinomas (EECs) with low-grade histology recur with poor outcomes. Published evidence suggests that poor outcomes may be associated with loss of expression of ER-alpha (ER-α) as well as with β-Catenin-1 (CTNNB1) and Kirsten rat sarcoma viral oncogene homolog (KRAS) mutations. This study reports on institutional experience with the incidence of recurrence in low-grade EEC and their association with CTNNB1 and KRAS mutations as well as estrogen/progesterone receptor (ER/PR)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Subsequent research has confirmed this association in the majority of studies, although not universally across all investigations [85,87,88]. Lastly, a strong association of CTNNB1 and KRAS mutations linking genotype to the type of recurrence was demonstrated in low-grade endometrioid endometrial carcinoma [89].…”
Section: Ctnnb1 Mutationmentioning
confidence: 88%
“…Subsequent research has confirmed this association in the majority of studies, although not universally across all investigations [85,87,88]. Lastly, a strong association of CTNNB1 and KRAS mutations linking genotype to the type of recurrence was demonstrated in low-grade endometrioid endometrial carcinoma [89].…”
Section: Ctnnb1 Mutationmentioning
confidence: 88%
“…Figure 7 shows the identified hub genes, signaling pathways, and biological processes that are potentially related to inflammation and ERα activation. KRAS gene mutations may lead to dysregulation in ERα activation that may lead to cancer proliferation, progression, tumor cell survival response, and metastasis [ 81 , 82 ]. In mice, SOS1 knock-down suppresses the Ras-ERK/P38MAPK/JNK pathway and induces epithelial-mesenchymal transition through NF-kB signaling, which may contribute to the metastasis of epithelial ovarian cancer cells [ 83 ].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of endometrial cancer increases with age and BMI ( 34 ); the first case in our report involved a 70-year-old patient with a history of DM, while the second case involved a 57-year-old patient with a BMI of 33 kg/m 2 . Evidence from a previous report indicated that DM is a poor prognostic factor in patients with low-grade EEC, specifically those with KRAS mutation ( 49 ). BMI and increases with age are the main risks of endometrial cancer; it has the strongest link to obesity among the 20 most common types of tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The immunohistochemistry staining of the primary tumor revealed medium positive expression of ER (50%) and PR (60%). According to a recent study, decreased expression of ER/PR detected by immunohistochemistry can serve as a valuable prognostic biomarker for identifying low-grade EEC that may have distant metastasis ( 49 ).…”
Section: Discussionmentioning
confidence: 99%